Green Concrete: Pemanfaatan Sampah Non Organik Tutup Botol “Kempyeng” Dan Serbuk Kaca Sebagai Material Susbtitusi Parsial Beton - Pranadiarso, Tedy; Junaidi, Imam; Ngibadah, Irsyadul (Fakultas Teknik, Universitas Wiraraja, 2025)
The construction industry in Indonesia continues to grow. Additionally, data from the Ministry of Environment shows that the amount of non-organic waste accumulated over the four years from 2020 to 2023 has also increased. The innovation in this study is the use of non-organic waste from ‘Kempyeng’ bottle caps and glass as a solution for environmentally friendly concrete (Green Concrete). This study aims to identification the optimal composition and analize percentage influence on compressive strength and bulk density from the use of non-organic waste bottle caps ‘Kempyeng’ and glass powder as partial substitutes for cement and gravel. The study used bottle cap ‘Kempyeng’ compositions of 0%, 2%, 4%, 5%, and 7%. Meanwhile, the glass powder mixture composition was 0%, 5%, and 8%. Laboratory test results showed the optimal composition for partial substitution of cement and gravel was 5% glass and 4% kempyeng, with concrete compressive strength at 28 days of 26.92 MPa and bulk density of 2360.7 kg/m³. This proportion also increased the compressive strength by 6.65% and reduced the bulk density by 0.82% compared to normal concrete. With these results, glass powder and ‘Kempyeng’ bottle caps can be used as partial substitutes for cement and gravel in concrete mixtures.